Pilipino translation of selected fairy tales for story reading to children in the lower primary grades - De Veyra, Jesusa S. 1934-
The primary purpose of this study is to translate selected fairy tales from the past and modern literature for children from English to Pilipino, which could be used by teachers to develop a genuine appreciation for literature through story reading, to stimulate critical thinking skills in the lower grades, and to supplement and enrich the amount of available literary materials in Pilipino which can be utilized in the free reading program of elementary schools.